2016
DOI: 10.1002/jmv.24547
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of platelet distribution width in patients with Crimean-Congo hemorrhagic fever

Abstract: Platelet distribution width (PDW) is a readily available blood test involving calculations performed by automated blood analyzers. Crimean-Congo hemorrhagic fever (CCHF) may exhibit a severe profile with fatal hemorrhaging or else present with a mild clinical process. The purpose of our study was to investigate the importance of PDW in CCHF patients and its clinical prognostic value. This study was conducted with patients with CCHF. Patients were divided into two groups on the basis of presence or absence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Yilmaz et al demonstrated PDW levels had significantly higher in adult patients with hemorrhagic CCHF compared with adult patients with nonhemorrhagic CCHF. 12 This situation may be due to different age groups and the severity of the study patients from ours.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Yilmaz et al demonstrated PDW levels had significantly higher in adult patients with hemorrhagic CCHF compared with adult patients with nonhemorrhagic CCHF. 12 This situation may be due to different age groups and the severity of the study patients from ours.…”
Section: Discussionmentioning
confidence: 85%
“…MPV, PDW, and MPM are markers of PLT activation and have been demonstrated to be a sign of inflammation, and these parameters can be obtained from the routine CBC test. 4,6,11,12,[16][17][18][19] MPV and PDW, most commonly used measure of PLT dimension, are usually ignored by the clinicians. 5,11 A study by Ekiz et al reported that MPV values were significantly increased in adult patients with CCHF compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…MPV represents the average size of platelets in the blood. An increase in PDW and MPV suggests an increased range of platelet size and increased average diameter of the platelets, respectively, due to swelling, destruction, and immaturity [ 12 , 13 , 15 21 ]. PCT is the ratio of total platelets in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased PLT count was shown to precede acute kidney failure in patients with Puumala virus infections [ 10 ], and PLT count was an independent predictor of severe HFRS [ 11 ] and critically ill patients in intensive care unit (ICU) [ 12 ]. In addition, PDW, MPV, P-LCR, and PCT are associated with platelet activation and function and have recently been shown to be useful markers for predicting occurrence and prognosis of certain inflammatory diseases and vascular diseases, such as Crimean-Congo hemorrhagic fever [ 13 ], sepsis [ 14 ], pulmonary embolism [ 15 ], ascitic fluid infection [ 16 ], obstructive sleep apnea [ 17 ], Crohn's disease [ 18 ], and coronary artery disease [ 19 ]. It is well known that platelet parameters are routinely tested on HFRS patients in hospitals almost every day.…”
Section: Introductionmentioning
confidence: 99%
“…[11] PDW gives information about the inflammatory processes of some diseases. [13,14] In the present study, we examined the relation between nasal polyps and PDW retrospectively in 99 patients who underwent endoscopic sinus surgery for nasal polyposis. The measurement of PDW is very easy and practical for several minutes with the result of CBC parameters of the autoanalyzer.…”
mentioning
confidence: 99%